2022
DOI: 10.1111/1750-3841.16414
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the different effects of sucrose, glucose, fructose, and a glucose–fructose mixture on wheat starch gelatinization, pasting, and retrogradation

Abstract: The gelatinization, pasting, and retrogradation of starch influence texture, quality, and shelf-life attributes of many foods. The purpose of this work was to document the effects of a 50:50 glucose:fructose (glc:fru) mixture and sucrose solutions on these starch traits to provide a fundamental basis to explain the different texture and shelf-life attributes of baked goods formulated with these sugars. Differential scanning calorimetry, rapid visco analyzer, and oscillatory rheometry were used to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Woodbury et al. investigated the effects of sucrose, glucose, fructose and a glucose/fructose mixture on wheat starch gelatinisation, pasting and retrogradation; subsequently, they found that sucrose and glucose inhibited wheat starch retrogradation, whereas fructose and a glucose/fructose mixture promoted amylopectin retrogradation (Woodbury et al ., 2023). However, to the best of our knowledge, most of these studies focused on the effects of sugars on the pasting and retrogradation of native starch (Guo & Du, 2014; Sun et al ., 2014; Wang et al ., 2016; Allan & Mauer, 2022; Woodbury & Mauer, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woodbury et al. investigated the effects of sucrose, glucose, fructose and a glucose/fructose mixture on wheat starch gelatinisation, pasting and retrogradation; subsequently, they found that sucrose and glucose inhibited wheat starch retrogradation, whereas fructose and a glucose/fructose mixture promoted amylopectin retrogradation (Woodbury et al ., 2023). However, to the best of our knowledge, most of these studies focused on the effects of sugars on the pasting and retrogradation of native starch (Guo & Du, 2014; Sun et al ., 2014; Wang et al ., 2016; Allan & Mauer, 2022; Woodbury & Mauer, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a suitable additive ensures the texture and quality of the products and increases the storage time (Yalcin & Basman, 2008; Wang et al ., 2015). Small molecular sugars are common additives that suppress starch retrogradation (Jang et al ., 2001; Woodbury et al ., 2023). Cairns et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution results in the formation of a thin layer of syrup. Low relative humidity causes moisture in the syrup to evaporate, causing the sugar to recrystallize at the surface and transferring moisture to other hygroscopic components (e.g., starch) (Chiravi et al, 2023;Woodbury et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is one of the ancient cereal crops cultivated worldwide, being a major source of carbohydrates for our daily life (Golea et al., 2023). Starch occupies about 65%–70% of the wheat grains, having a vital role in the structure and nutrition of manufactured foods (Woodbury et al., 2023). Therefore, understanding of the structure–property relations for starch is crucial for both food manufacturers and consumers.…”
Section: Introductionmentioning
confidence: 99%